2022
DOI: 10.1186/s12944-022-01669-z
|View full text |Cite
|
Sign up to set email alerts
|

The associations between serum high-density lipoprotein cholesterol levels and malignant behavior in pancreatic neuroendocrine neoplasms

Abstract: Background The role of serum high-density lipoprotein cholesterol (HDL-c) in tumorigenesis are observed in several endocrine-related cancers. However, its role in pancreatic neuroendocrine neoplasms (PNENs) has not been understood. In the current study, the relationship between HDL-c levels and malignant behavior in PNENs was explored. Methods One hundred ninety-seven patients with histopathology confirmed PNENs were included. PNENs were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…A recent study showed that triglycerides (TG)/high-density lipoprotein (HDL) ratio may have potential in identifying bladder cancer [4]. Low serum HDL levels are also associated with malignant behavior of pancreatic neuroendocrine neoplasms [14]. In addition, studies also showed that oxidized low-density lipoprotein-cholesterol (LDL-c), or high total serum cholesterol (TC) and HDLcholesterol (HDL-c) was associated with more aggressive cancer [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that triglycerides (TG)/high-density lipoprotein (HDL) ratio may have potential in identifying bladder cancer [4]. Low serum HDL levels are also associated with malignant behavior of pancreatic neuroendocrine neoplasms [14]. In addition, studies also showed that oxidized low-density lipoprotein-cholesterol (LDL-c), or high total serum cholesterol (TC) and HDLcholesterol (HDL-c) was associated with more aggressive cancer [15,16].…”
Section: Introductionmentioning
confidence: 99%